Lanna Food: The Cultural Management Strategy for the Creative Economy Development - Thongmee, Onanong; Rodhetbhai, Chamnan; Siltragool, Wisanee (Humanities, Arts and Social Sciences Studies, 2015)
The study of local wisdom for the production and development of Lanna food, a reference to local food of the upper northern region of Thailand, provides great benefits towards the creative economy and sustainable business, and also promotes conservation of Lanna food. This research aims to (1) study the history and the culture of Lanna food (2) study problems and solution guidelines of Lanna food, and (3) study the cultural management of Lanna food in order to develop the creative economy. A qualitative research method was applied in this research, with the districts in Chiang Mai Province as target areas, namely: Mueang, Fang, Chiang Dao, San Pa Tong, Hang Dong, Mae Taeng, Doi Lo, Phrao, Doi Saket, Mae Wang, Wiang Haeng, and San Sai. The research instruments of this study, employed in field data collection from key informants, casual informants, and general informants, included interview, observation, focus group discussion, and workshops. Documentary approach was also used to collect data. In terms of the verification of the aforesaid data, triangulation method was used, while a review of descriptive data analysis was chosen as a means of the presentation of research findings. In terms of the guidelines for the cultural management of Lanna food to develop the creative economy, it was found that the producers coped with the cultural management of Lanna food as follow. Producers should select the products and participate in the OTOP Product Champion (OPC) campaign which held every two years, in order to maintain quality and standard of the products. Apart from that, a creative economy framework should be applied in order to develop the creative economy which consists of local wisdom, the Lanna food identity, appropriate technology, and distinctive services with the application of outstanding package design that would help increasing the value and prices of the products. This would contribute to job creation, competitive competence and healthy consumption. All in all, these practices would improve Lanna food as a means to create job opportunities, provide a stable income, and develop a creative economy in the community. In conclusion, Lanna food contributes to the creative economy of the community and the country. Therefore, both the public and private sectors should recognize its importance and promote Lanna food by means of academic and financial support in order to ensure the cultural conservation and effective management for the sustainability of Lanna food.